Microbial Eukaryotes that Lack Sterols. (7th June 2017) - Takishita, Kiyotaka; Chikaraishi, Yoshito; Tanifuji, Goro; Ohkouchi, Naohiko; Hashimoto, Tetsuo; Fujikura, Katsunori; Roger, Andrew J.
Abstract: It is widely held that sterols are key cyclic triterpenoid lipids in eukaryotic cell membranes and are synthesized through oxygen‐dependent multienzyme pathways. However, there are known exceptions―ciliated protozoans, such as Tetrahymena, along with diverse low‐oxygen‐adapted eukaryotes produce, instead of sterols, the cyclic triterpenoid lipid tetrahymanol that does not require molecular oxygen for its biosynthesis. Here, we report that a number of anaerobic microbial eukaryotes (protists) utilize neither sterols nor tetrahymanol in their membranes. The lack of detectable sterol‐like compounds in their membranes may provide an opportunity to reconsider the physiological function of sterols and sterol‐like lipids in eukaryotes.